Consumer Trust as the Key: Analysis of Its Influence on Online Purchase Interest in the Marketplace - Arif Sudaryana; Santi Lila Erlanggi; Pradita Nindya Aryandha (Department of Management, Universitas PGRI Yogyakarta., 2025)
Purpose: This study aims to analyze the effect of consumer trust on online purchase interest in the marketplace. Methodology: The method used in this research is a descriptive quantitative research method. The population in this study is the consumer marketplace users in the Special Region of Yogyakarta, and the sample in this study is 120 respondents. The sampling method in this technique uses purposive sampling. Purposive sampling is a method of selecting samples based on certain criteria. The criteria in this study are marketplace users in Yogyakarta who have purchased in the marketplace. Data analysis methods include validity, reliability, multiple regression analysis, hypothesis testing through the coefficient of determination (R2), F test, and t test. Findings: The results of the study found that ability had a positive and insignificant effect on purchase interest, benevolence has a positive and significant effect on purchase interest, integrity has a positive and insignificant effect on purchase interest, Reputation has a positive and significant effect on purchase interest in the marketplace, also the website quality has a positive and significant effect on purchase interest. The five independent variables jointly affect consumer purchase interest in the marketplace; the calculated F value is 20.686 with a significance of 0.000 < 0.05. The magnitude of the influence of ability, benevolence, integrity, reputation, and website quality on purchase interest is 45,3%. Originality: Unresearched geographic focus and empirical findings that benevolence, reputation, and website quality have a significant influence on purchase intention. With this approach, this study contributes to enriching the literature on the local e-commerce context, especially in Indonesia, as well as broadening the understanding of the determinants of consumer purchase intention from the perspective of trust and digital quality. Practical Implications: Marketplaces need to improve aspects of benevolence, reputation, and website quality, because these three aspects have been proven to have a significant influence on consumer purchasing interest, which has not been discussed simultaneously in previous studies